1996
DOI: 10.1210/edrv-17-5-481
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and the Insulin-Like Growth Factor System in Myogenesis*

Abstract: It is very clear that the GH-IGF axis plays a major role in controlling the growth and differentiation of skeletal muscles, as it does virtually all of the tissues in the animal body. One aspect of this control is unquestioned: circulating GH acts on the liver to stimulate expression of the IGF-I and IGFBP3 genes, substantially increasing the levels of these proteins in the circulation. It also seems that GH stimulates expression of IGF-I genes in skeletal muscle, although there are a number of cases in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
373
0
16

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 527 publications
(404 citation statements)
references
References 0 publications
15
373
0
16
Order By: Relevance
“…However, the stimulation of myogenic differentiation by the IGFs has been demonstrated independently in a number of laboratories (reviewed in Ref. 1), and the effect is now well established although not fully explained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the stimulation of myogenic differentiation by the IGFs has been demonstrated independently in a number of laboratories (reviewed in Ref. 1), and the effect is now well established although not fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…However, the insulin-like growth factors (IGF-I and IGF-II) 1 are unique among growth factors in that they stimulate both proliferation and differentiation of muscle cells in culture. Recently, it has been shown that IGF actions occur through two phases (reviewed in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor-I (IGF-I) is therefore unique among growth factors as it stimulates both proliferation and differentiation of skeletal-muscle cells in culture [1][2][3][4][5][6][7]. In normal cell division, most cell lines require IGF-I, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IGFAbbreviations used : IGF-I, insulin-like growth factor-I ; IRES, internal ribosome-entry site ; GFP, green fluorescent protein ; DMEM, Dulbecco's modified Eagle's medium ; K s , fractional synthesis rate ; ALT, alanine aminotransferase ; LDH, lactate dehydrogenase ; MNF, myocyte nuclear factor ; MRF, myogenic regulatory factor. 1 To whom correspondence should be addressed (e-mail b.graham!victorchang.unsw.edu.au).…”
Section: Introductionmentioning
confidence: 99%